2021
DOI: 10.1371/journal.pone.0247448
|View full text |Cite
|
Sign up to set email alerts
|

Spatial navigation with horizontally spatialized sounds in early and late blind individuals

Abstract: Blind individuals often report difficulties to navigate and to detect objects placed outside their peri-personal space. Although classical sensory substitution devices could be helpful in this respect, these devices often give a complex signal which requires intensive training to analyze. New devices that provide a less complex output signal are therefore needed. Here, we evaluate a smartphone-based sensory substitution device that offers navigation guidance based on strictly spatial cues in the form of horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The study design and the experimental setup were inspired by a proposal of a standardised obstacle course for assessment of "visual function in ultra low vision and artificial vision" [63] but has been adapted due to spatial constraints and selected study objectives (e.g., testing with two groups and limited task scope only). There are two further studies suggesting a very similar setup for testing sensory substitution devices [64,65] that were not considered for the choice of this study design.…”
Section: Trial Sessionsmentioning
confidence: 99%
“…The study design and the experimental setup were inspired by a proposal of a standardised obstacle course for assessment of "visual function in ultra low vision and artificial vision" [63] but has been adapted due to spatial constraints and selected study objectives (e.g., testing with two groups and limited task scope only). There are two further studies suggesting a very similar setup for testing sensory substitution devices [64,65] that were not considered for the choice of this study design.…”
Section: Trial Sessionsmentioning
confidence: 99%
“…Overall detection, avoidance, and identification performances were not statistically different between groups. This result might be surprising given the established literature on sensory substitution showing superior abilities of EB [34], but some studies on minimalist SSDs (Guidance-SSD; Sound of Vision) have also observed equivalent performances of EB, LB, and SC [24,35,36]. One might thus suppose that our findings of efficient performances for every group despite only brief training may be an indicator of the device's simplicity and ease of use [37].…”
Section: Influence Of Visual Experiencementioning
confidence: 66%
“…The program creates indoor maps by monitoring a sighted person’s activities inside of the facility, develops and prints QR code location markers for locations of interest, and then gives blind users vocal direction. Pare et al [ 90 ] investigated a smartphone-based sensory replacement device that provides navigation direction based on strictly spatial signals in the form of horizontally spatialized sounds. The system employs numerous sensors to identify impediments in front of the user at a distance or to generate a 3D map of the environment and provide audio feedback to the user.…”
Section: Related Workmentioning
confidence: 99%